Closing the loop or squaring the circle? Locating generative spaces for the circular economy - Hobson, Kersty (Progress in human geography, 2016)
Heightened concerns about long-term sustainability have of late enlivened debates around the circular economy (CE). Defined as a series of restorative and regenerative industrial systems, parallel socio-cultural transformations have arguably received less consideration to date. In response, this paper examines the contributions human geographical scholarship can make to CE debates, focusing on ‘generative spaces’ of diverse CE practices. Concepts infrequently discussed within human geography such as product service systems and ‘prosumption’ are explored, to argue that productive potential exists in bringing these ideas into conversation with ongoing human geographical research into practices, materialities, emergent political spaces and ‘everyday activism’.